First study on the outcomes of biliopancreatic diversion with duodenal switch in Chinese patients with obesity - Wang, Lun; Zhang, Zheng; Wang, Zeyu; Jiang, Tao (Frontiers in Surgery, 2023)
Background Biliopancreatic diversion with duodenal switch (BPD-DS) is a bariatric procedure used in the treatment of obesity and related metabolic disorders. However, to date, the data on BPD-DS among Chinese patients with obesity is completely lacking. Objective This is the first study to evaluate the safety and efficacy of BPD-DS in the treatment of Chinese patients with obesity. Methods Data from 12 patients undergoing BPD-DS between September 2019 and March 2020 were analyzed retrospectively to evaluate complications, weight loss, comorbidity resolution, and nutritional status. Results All patients completed the 1-year follow-up. There was no conversion to laparotomy or death. Mean operative time was 257.08 ± 29.27 min. The median length of stay was 7 days (ranging from 4–38 days). Complications occurred in three patients. The 1-year body mass index was 25.13 ± 4.71 kg/m2 with a mean excess weight loss of 100.11 ± 33.29% and a mean total weight loss of 43.22 ± 7.71%. Remission was achieved in 100% (7/7 cases) for type 2 diabetes, in 83.3% (10/12 cases) for hypertension, and in 62.5% (5/8 cases) for hyperuricemia. At 1 year after BPD-DS, the prevalence of albumin deficiency was 16.7%, for iron deficiency was 16.7%, and for zinc deficiency was 50%. There were 8.3% of the patients who were anemic. High deficiency rates for vitamins were presented mainly in vitamin A and vitamin E: vitamin A in 58.3% of the patients and vitamin E in 50% of the patients. The prevalence of asymptomatic gallstones increased significantly from 0% preoperatively to 41.7% postoperatively. Conclusion BPD-DS had excellent weight loss and resolution of comorbidities among Chinese patients with obesity. However, high rates of nutritional deficiencies and complications were found after BPD-DS, especially for vitamin A and vitamin E.